Improvement of rice production through combined use of organic manures and bio-slurries with chemical fertilizers (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The field experiment was conducted at the Soil Science Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period of February to May 2015 to evaluate the effect of organic manures and bio-slurries with chemical fertilizers on the improvement of rice production in Old Brahmaputra Floodplain soils. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. There were eight treatment combinations viz. T0: Control (no fertilizer or manure), T1: Farmers’ practice, T2: 100% RFD chemical fertilizers (NPKSZnB), T3: 75% RFD (NPKSZnB) + CD (5 t ha-1), T4: 75% RFD (NPKSZnB) + CD slurry (5 t ha-1), T5: 75% RFD (NPKSZnB) + PM (3 t ha-1), T6: 75% RFD (NPKSZnB) + PM slurry (3 t ha-1), T7: 75% RFD (NPKSZnB) + Compost (10 t ha-1). The rice crop cv. BRRI dhan29 was used as a test crop. Result showed that most of the growth and yield components of rice viz. plant height, effective tillers, panicle length, grains per panicle and 1000-grain weight were significantly influenced due to application of organic manures and bio-slurries with chemical fertilizers. Application of chemical fertilizers alone or in combination with organic manures or bio-slurries resulted in a significant increase in grain and straw yields of rice. Treatments 100% RFD chemical fertilizers (NPKSZnB) as well as 75% RFD (NPKSZnB) + PM slurry (3 t ha-1) showed better performances than other treatments. Nutrient uptake by rice was also significantly affected by different treatments. Therefore, treatment (T6) 75% RFD (NPKSZnB) + PM slurry (3 t ha-1) could be the best option to increase crop yield in Old Brahmaputra Floodplain soils.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 78-85